Mass transfer of elements in the undersurface layers under combined treatment by pulsed ion beams and plasma flows; Korus 2001; Vol. 1 - Petrov A. V.; Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich; Struts V. K.; Tolmacheva V. G.; Usov Y. P. Yuri Petrovich; Shulepov I. A. Ivan Anisimovich (2001, 2001)
Results are presented for some processes occurring at different stages of strong adhesion of coatings and modified layers creation with the use of high-dose implantation and deep diffusive doping of elements under pulsed energetic impact. The investigations have been carried out to consider the possibility of combined materials treatment with pulsed ion beams of power density ranging from 103 to 108 W/cm2. The facility includes the accelerator of high-power ion beams and the sources of repetitively-pulsed metal ion beams and metal plasma flows.